Detection of circulating Paracoccidioides brasiliensis antigen in urine of paracoccidioidomycosis patients before and during treatment - Salina, Margarete Aparecida [UNESP]; Shikanai-Yasuda, Maria Aparecida; Mendes, Rinaldo Poncio [UNESP]; Barraviera, Benedito [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (My University, 1998)
For the diagnosis and follow-up of paracoccidioidomycosis patients undergoing therapy, we evaluated two methods (immunoblotting and competition enzyme immunoassay) for the detection of circulating antigen in urine samples. A complex pattern of reactivity was observed in the immunoblot test. Bands of 70 and 43 kDa were detected more often in urine samples from patients before treatment. The immunoblot method detected gp43 and gp70 separately or concurrently in 11 (91.7%) of 12 patients, whereas the competition enzyme immunoassay detected antigenuria in 9 (75%) of 12 patients. Both tests appeared to be highly specific (100%), considering that neither fraction detectable by immunoblotting was present in urine samples from the control group. gp43 remained present in the urine samples collected during the treatment period, with a significant decrease in reactivity in samples collected during clinical recovery and increased reactivity in samples collected during relapses. Reactivity of some bands was also detected in urine specimens from patients with 'apparent cure.' The detection of Paracoccidioides brasiliensis antigens in urine appears to be a promising method for diagnosing infection, for evaluating the efficacy of treatment, and for detecting relapse.
Keywords: antigen detection; clinical article; diagnostic value; enzyme immunoassay; human; immunoblotting; paracoccidioides brasiliensis; priority journal; recurrence risk; reinfection; south american blastomycosis; urinalysis; Antifungal Agents; Antigens, Fungal; Humans; Immunoblotting; Immunoenzyme Techniques; Paracoccidioides; Paracoccidioidomycosis; Recurrence; Sensitivity and Specificity; Paracoccidioides brasiliensis